2017
DOI: 10.24200/sci.2017.4524
|View full text |Cite
|
Sign up to set email alerts
|

Phenol Removal from Aqueous Solution by Adsorption Process: Study of The Nanoparticles Performance Prepared from Alo vera and Mesquite (Prosopis) Leaves

Abstract: Abstract. This study was performed to measure the potential utilization of agro-waste to generate nanoparticles and evaluate its capability as a low-cost adsorbent for phenol removal. Adsorption studies for phenol removal using aloe vera and mesquite leaves nanoparticles were carried out under various experimental conditions including pH, nanobioadsorbent dosage, phenol concentration, contact time, temperature, and ionic strength in a batch reactor. The adsorption kinetics were applied by pseudo-rst order and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Moreover, desorption study by deploying ethanol-treatment showed that the reusability of this matters was around half of its initial content. Eventually, plant leaves named aloe vera and mesquite leave were also reported dependable as sorbent alternative for purging phenol especially at neutral pH [70].…”
Section: Leaves-based Sorbentmentioning
confidence: 99%
“…Moreover, desorption study by deploying ethanol-treatment showed that the reusability of this matters was around half of its initial content. Eventually, plant leaves named aloe vera and mesquite leave were also reported dependable as sorbent alternative for purging phenol especially at neutral pH [70].…”
Section: Leaves-based Sorbentmentioning
confidence: 99%
“…The final adsorbent materials were crushed and sieved (<180 µm). The obtained adsorbent showed biosorption capacity of 356 mg/g [66]. For the same dye, significant removal efficiency (98%) was obtained with reduced graphene oxide using AV [64].…”
Section: Aloe Vera As Biosorbent For Pollutant Removalmentioning
confidence: 87%
“…Phenol in water is partially dissociated into phenoxide ion and, its solubility increases as the ionic strength increases (salting-out effect). [31] However, it is worthwhile to note that benzene was absorbed by n-sPS aerogel with an absorption efficiency of approximately 70%. Similar result was obtained considering a binary toluenephenol aqueous solution in presence of NaCl (Figure 4b).…”
Section: Benzene Toluene and Phenol Absorption In N-sps Aerogelsmentioning
confidence: 99%